#TITLE_ALTERNATIVE# - PASHA NIM : 21816005, RANDY
This study aims to optimize the determining factors of HBsAg adsorption onto aluminum hydroxide adjuvant and HBsAg content in the Hepatitis B vaccine formulation. The acceptance criteria of the product are adsorption level (Y1) ≥99.5% and HBsAg content (Y2) ≥19.55 μg/mL The steps of this research included: risk assessment using failure mode and effect analysis (FMEA), screening for significant factors using Ã‚Â¼-fractional factorial design, response optimization and design space determination using Box Behnken design. There were five high-risk factors with RPN ≥60 identified by FMEA, namely: the ratio of adjuvant and antigen (X1), buffer pH (X2), formulation process temperature (X3), mixing duration (X4), and adjuvant type (X5). Factorial design analysis showed that X1, X2, and X3 as the factors that influence the product. The optimum result of Response Surface Method Ã‚Â–Box Behnken Design were Y1=99.8% and Y2=20.9 μg/mL, which was found at X1=22.63, X2=7.0, and X3 =10 o C. The design space to fulfill product criteria was in the range of X1=20Ã‚Â–25, X2=6.7Ã‚Â– 7.0, and X3=10Ã‚Â–20 o C. To conclude, the optimum factors of the formulation and preparation of Hepatitis B vaccine containing aluminum hydroxide adjuvant were successfully determined.